2017
DOI: 10.1007/s11606-017-4152-5
|View full text |Cite
|
Sign up to set email alerts
|

An Evidence Map of the Women Veterans’ Health Research Literature (2008–2015)

Abstract: BackgroundWomen comprise a growing proportion of Veterans seeking care at Veterans Affairs (VA) healthcare facilities. VA initiatives have accelerated changes in services for female Veterans, yet the corresponding literature has not been systematically reviewed since 2008. In 2015, VA Women’s Health Services and the VA Women’s Health Research Network requested an updated literature review to facilitate policy and research planning.MethodsThe Minneapolis VA Evidence-based Synthesis Program performed a systemati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(48 citation statements)
references
References 458 publications
2
43
0
Order By: Relevance
“…The prevalence of hypertension and high cholesterol among women veterans was strikingly high (>44% in women ages 45-64 years and >60% in women ages !65 years), consistent with previous studies (Vimalananda et al, 2013). Given the predominance of hypertension and diabetes observed in women veterans, it is remarkable that the Danan et al (2017) review of women veterans' health did not identify any published clinical research studies with a primary focus on hypertension and only three studies on diabetes that included women veterans.…”
Section: Discussionsupporting
confidence: 84%
See 3 more Smart Citations
“…The prevalence of hypertension and high cholesterol among women veterans was strikingly high (>44% in women ages 45-64 years and >60% in women ages !65 years), consistent with previous studies (Vimalananda et al, 2013). Given the predominance of hypertension and diabetes observed in women veterans, it is remarkable that the Danan et al (2017) review of women veterans' health did not identify any published clinical research studies with a primary focus on hypertension and only three studies on diabetes that included women veterans.…”
Section: Discussionsupporting
confidence: 84%
“…One notable gender difference that is supported by the literature is that depressive disorders, PTSD, and anxiety disorders are more prevalent among women compared with men across the lifespan Lehavot et al, 2018;Maguen et al, 2010;Runnals et al, 2014;Ziobrowski et al, 2017). Consistent with , depression was among the most commonly reported conditions by women veterans across the lifespan; despite depression's high prevalence, the Danan et al (2017) review found only three studies including women veterans with a primary focus on depression. In addition, women exhibited a substantially higher prevalence of osteoporosis, thyroid problems, irritable bowel syndrome, migraine headaches, osteoarthritis, and asthma (RRs, 1.9-4.2), which is comparable with findings from a nationally representative sample of U.S. veterans (Ziobrowski et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…To do so, challenges that women Veterans face, such as rural/urban disparities in health and access to healthcare as well as other barriers to receiving VHA services, should be considered . These challenges do still exist in improving women Veterans’ health despite significant progress made over the last years . For example, HRQoL of women Veterans can be influenced by social, emotional, physical, and other factors .…”
Section: Discussionmentioning
confidence: 99%